Association of obstructive sleep apnea with adverse pregnancy-related outcomes in military hospitals. (March 2017) - Spence, Dennis L.; Allen, Rhonda C.; Lutgendorf, Monica A.; Gary, Virginia R.; Richard, John D.; Gonzalez, Sara C.
Abstract: Background: Obstructive sleep apnea (OSA) is associated with significant morbidity and mortality in non-obstetrical and obstetrical patients. Objectives: To estimate the prevalence of OSA and its relationship with pregnancy-related complications in a general obstetric population of Department of Defense beneficiaries receiving direct-care at military treatment facilities. Study design: A retrospective cohort study of all women (N = 305, 001) who gave birth at a military treatment facility from 2008 to 2014. OSA cases were randomly selected and matched on age (3:1 ratio) to non OSA cases. Multivariable logistic regression was used to examine the risks of adverse pregnancy outcomes (cesarean delivery, gestational diabetes, gestational hypertension, preeclampsia, postoperative wound complications, hospital stay greater than five days, acute renal failure, pulmonary edema, preterm delivery, poor fetal growth, and stillbirth) between pregnant women with and without a diagnosis of OSA. Cases were identified using ICD-9 codes, while controlling for demographics, obesity, and medical comorbidities associated with OSA and the outcomes of interest. Results: We identified 266 cases of OSA (OSA rate = 8.7 per 10, 000; increased from 6.4 to 9.9 per 10, 000 from 2009 to 2013). OSA was associated with a higher odds of cesarean delivery (AOR, 1.60; 95% CI, 1.06–2.40), gestational hypertension, (AOR, 2.46; 95% CI, 1.30–4.68), preeclampsia (AOR, 2.42; 95% CI, 1.43–4.09), and preterm delivery (AOR, 1.90; 95% CI, 1.09–3.30). Conclusions: Obstructive sleep apnea is associated with adverse maternal and fetal outcomes.